Developmental Origins of Rumination in Middle Childhood: The Roles of Early Temperament and Positive Parenting - Schweizer, Tina H. (J Clin Child Adolesc Psychol, 2017)
OBJECTIVE: Rumination, a thinking style characterized by a repetitive inward focus on negative cognitions, has been linked to internalizing disorders, particularly depression. Moreover, research suggests that rumination may be a cognitive vulnerability that predisposes individuals to psychopathology. Surprisingly little is known, however, about the etiology and development of rumination. The present study examined the role of specific components of child temperamental negative emotionality (sadness, fear, anger) and effortful control (inhibition) as well as parenting behaviors during early childhood in the development of rumination in middle childhood. METHOD: Early childhood (age 3) temperament and parenting behaviors were assessed observationally and rumination was self-reported in middle childhood (age 9) in a large community sample (N=425; 47.1% female). RESULTS: Two significant interactions emerged. First, temperamental anger interacted with IC such that high anger and low IC predicted higher levels of rumination, whereas low anger and low IC predicted lower levels of rumination. Second, IC interacted with parenting such that children with low IC and positive parenting had lower levels of rumination. In contrast, children with high IC reported similar levels of rumination regardless of parenting quality. CONCLUSIONS: Overall, these findings highlight the interplay of early IC with temperamental anger and positive parenting in the development of ruminative tendencies in middle childhood.